Genetic analysis of the Drosophila alphaPS2 integrin subunit reveals discrete adhesive, morphogenetic and sarcomeric functions. - Bloor, J.W.; Brown, N.H. (Genetics, 1998)
The integrin family of cell surface receptors mediates cell-substrate and cell-to-cell adhesion and transmits intracellular signals. In Drosophila there is good evidence for an adhesive role of integrins, but evidence for integrin signalling has remained elusive. Each integrin is an alphabeta heterodimer, and the Drosophila betaPS subunit forms at least two integrins by association with different alpha subunits: alphaPS1betaPS (PS1) and alphaPS2betaPS (PS2). The complex pattern of PS2 integrin expression includes, but is more extensive than, the sites where PS2 has a known requirement. In order to investigate whether PS2 integrin is required at these additional sites and/or has functions besides mediating adhesion, a comprehensive genetic analysis of inflated, the gene that encodes alphaPS2, was performed. We isolated 35 new inflated alleles, and obtained 10 alleles from our colleagues. The majority of alleles are amorphs (36/45) or hypomorphs (4/45), but five alleles that affect specific developmental processes were identified. Interallelic complementation between these alleles suggests that some may affect distinct functional domains of the alphaPS2 protein, which specify particular interactions that promote adhesion or signalling. One new allele reveals that the PS2 integrin is required for the development of the adult halteres and legs as well as the wing.